2022
DOI: 10.1007/s11886-022-01796-0
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nurse Practitioners in the Management of Heart Failure Patients and Programs

Abstract: Purpose of Review The goal of this paper is to highlight the multifaceted approach heart failure (HF) nurse practitioners (NPs) use to manage patients. We were seeking to answer if NPs have the scope of clinical skills to manage the complexity of HF patients. Recent Findings NP care in HF has been shown to reduce readmissions, improve timeliness of visits, decrease cost, and improve quality outcomes in small heterogeneous studies. Summary The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…NPs, as licensed healthcare professionals, provide comprehensive, patient-centered care that improves patient self-care awareness and quality. Their roles include diagnosing and treating patients, prescribing medications, making referrals, managing acute and chronic conditions, and focusing on health promotion, disease prevention, and patient satisfaction [ 99 ]. A cohort study during the COVID-19 pandemic demonstrated that an NP-led pilot telehealth program enabled 75% of patients with HF to achieve optimal GDMT within 2 months, with a significant improvement in the left ventricular ejection fraction observed in 77% of patients during follow-up [ 100 ].…”
Section: Subgroups Of Patients With Hf and Gdmt Explorationmentioning
confidence: 99%
“…NPs, as licensed healthcare professionals, provide comprehensive, patient-centered care that improves patient self-care awareness and quality. Their roles include diagnosing and treating patients, prescribing medications, making referrals, managing acute and chronic conditions, and focusing on health promotion, disease prevention, and patient satisfaction [ 99 ]. A cohort study during the COVID-19 pandemic demonstrated that an NP-led pilot telehealth program enabled 75% of patients with HF to achieve optimal GDMT within 2 months, with a significant improvement in the left ventricular ejection fraction observed in 77% of patients during follow-up [ 100 ].…”
Section: Subgroups Of Patients With Hf and Gdmt Explorationmentioning
confidence: 99%
“…Initially, the increased thickness of the ventricular walls compensates for an increased workload. However, it can impair diastolic function over time and contribute to heart failure [14]. Systolic dysfunction, characterized by reduced ejection fraction, is a hallmark of HFrEF.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Likewise, those who had radiation therapy for malignancies in the chest or middle of the chest are at risk of developing radiation-induced heart disease, which is marked by anomalies in the heart valves and the arteries that provide blood to the heart. Identifying these particular connections is essential for customizing surveillance and preventive measures to address the distinct cardiovascular risks linked to various cancer treatments [ 14 ].…”
Section: Reviewmentioning
confidence: 99%
“…Identifying groups of cancer patients who are at high risk for cardiovascular problems is crucial for implementing specific preventative measures and individualized healthcare strategies [ 14 ]. Multiple factors contribute to identifying individuals who are at a heightened risk of experiencing cardiovascular issues either during or after undergoing cancer therapy.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation